Changes in Chinese hair growth along a full year. (3rd September 2014) - Liu, C.; Yang, J.; Qu, L.; Gu, M.; Liu, Y.; Gao, J.; Collaudin, C.; Loussouarn, G.
Synopsis: Objective: To confirm the existence of seasonal hair growth cycle among Chinese subjects and objectivize the seasonal effect of hair loss; the hair growth parameters of Chinese volunteers were followed monthly for an entire year on the same area of vertex. Methods: The hair growth parameters of 41 Chinese volunteers (women and men), free from alopecia, were recorded monthly along an entire year using the phototrichogram technique. Results: Results show an increased rate of telogen hairs (growing arrest) around August–September in the study group, as previously reported in European subjects albeit of a lower extent and remaining within the normal range of healthy head hair parameters. The possible effects of latitude and daylight duration are discussed. Conclusion: Data confirm that Chinese hairs present characteristics of the most developed and fast growing terminal fibres, as compared to other non‐Asian ethnics.